Perlindungan Hukum Pemenang Lelang Eksekusi Hak Tanggungan dalam Sengketa Penguasaan Objek oleh Debitur - Arrol Vastie Prabamantya; Soegianto Soegianto (Pusat Riset dan Inovasi Nasional, 2025)
This research discusses the legal protection of the winner of the mortgage execution auction in the dispute over the control of the object by the debtor, focusing on three problem formulations: the legal position of the auction winner, the form of legal protection available, and the role and responsibility of the judiciary in resolving the dispute. The method used is empiri juridical with an analytical descriptive approach, which examines legal norms and their implementation in practice. Data were obtained through literature study and analyzed qualitatively based on theory and applicable laws and regulations. The results showed that the winner of the auction has a legal position and is in good faith. legal position and good faith, but often face obstacles due to the physical control of the object by the debtor, which creates legal uncertainty. Legal protection provided by the state must be implementative, not only normative, through mechanisms such as execution, lawsuit, mediation, and compensation. The judiciary has an important role in enforcing and implementing the rights of the winner of the auction, so that justice and legal certainty can be achieved. auction winners, so that justice and legal certainty can be realized effectively.